Catalytic challenges and strategies for the carbonylation of σ-bonds. Issue 2 (20th January 2021) - Nasr Allah, Tawfiq; Ponsard, Louise; Nicolas, Emmanuel; Cantat, Thibault
Abstract : Direct catalytic insertion of carbon monoxide in chemicals poses the challenge of controlling both the σ-bond activation and the subsequent carbonylation. Abstract : The carbene character of carbon monoxide offers the possibility to utilize this C1 -building block for the carbonylation of a variety of organic substrates by insertion of CO into σ-bonds. Although presenting an ideal atom economy this route requires the design and utilization of reactive catalysts able to activate strong C–O, C–N, and C–H bonds in the presence of carbon monoxide. This perspective article addresses, in the context of sustainable chemistry, the challenges and strategies facing the catalytic carbonylation of σ-bonds and presents the key advances in the field over the last few decades, for the carbonylation polar and apolar substrates, such as the conversion of alcohols to formates and esters and the carbonylation of amines to amides.